2022
DOI: 10.3390/ijms23168935
|View full text |Cite
|
Sign up to set email alerts
|

Congo Red as a Supramolecular Carrier System for Doxorubicin: An Approach to Understanding the Mechanism of Action

Abstract: The uptake and distribution of doxorubicin in the MCF7 line of breast-cancer cells were monitored by Raman measurements. It was demonstrated that bioavailability of doxorubicin can be significantly enhanced by applying Congo red. To understand the mechanism of doxorubicin delivery by Congo red supramolecular carriers, additional monolayer measurements and molecular dynamics simulations on model membranes were undertaken. Acting as molecular scissors, Congo red particles cut doxorubicin aggregates and incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This observation points towards a conclusion that the membrane has to be in a relaxed state in order for CR entry to occur. This is in agreement with our previous simulations with ordered DPPC membranes [35], where spontaneous entry was not observed. MD simulations show that the affinity of CR towards the membrane is rooted in the cooperation of electrostatic and van der Waals forces.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This observation points towards a conclusion that the membrane has to be in a relaxed state in order for CR entry to occur. This is in agreement with our previous simulations with ordered DPPC membranes [35], where spontaneous entry was not observed. MD simulations show that the affinity of CR towards the membrane is rooted in the cooperation of electrostatic and van der Waals forces.…”
Section: Discussionsupporting
confidence: 94%
“…In this respect, the active role of CR in promoting the transfer of doxorubicin through the headgroups region is an important finding. In our previous study, where DPPC membranes were used, we concluded that the main role of CR in promoting DOX uptake by MCF7 cells lies in the change in the aggregation patterns of DOX in water [ 35 ], namely, in the presence of CR, the bioavailability of DOX was increased by incorporating DOX molecules into the DOX + CR clusters and increasing the drug’s solubility. Spontaneous penetration of the DPPC membrane by either CR or DOX + CR clusters was not observed in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that both compounds have the ability to penetrate cells [ 35 , 53 ] and cause changes in signaling pathways. Our study demonstrated that treatment of RT4 and T24 bladder cancer cells with sorafenib or CR-BAY 5:1 reduced Akt and Erk phosphorylation, which may be closely related to the decrease in proliferation and induction of apoptosis we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This compound is known as a dye, e.g., in the diagnosis of amyloidosis. However, its supramolecular structure and the ability to react with anti-cancer compounds is undoubtedly an innovative approach in targeted therapy [ 34 , 35 ]. Studies show that well-known colloidal drug aggregators (including sorafenib) can be co-formulated with bis-azo dyes to form colloids that are much more stable and much more monodisperse than colloidal aggregates.…”
Section: Introductionmentioning
confidence: 99%